Improving Quality of Human Resources through HRM Practices and Knowledge Sharing - Salman Iqbal; Ivan Litvaj; Mário Drbúl; Mamoona Rasheed (Administrative Sciences, 2023)
One of the objectives of this paper is to examine the empirical effects of certain Human Resource Management (HRM) practices and reciprocity as antecedents of knowledge-sharing (KS) behavior. In an organization, human resource knowledge quality plays a key role in the effective performance of the organization by communicating their knowledge with management and co-workers to perform their tasks in a better way. This is possible only when useful and relevant quality knowledge is successfully shared. Despite various studies on this topic, there is little research on KS and HRM practices in developing countries like Pakistan. A survey-based approach is used for data collection from different employees in the banking sector of Pakistan. The hypotheses are formulated based on the four HRM practices and reciprocity. The dataset is critically investigated using structural equation modeling (SEM). The results of this study suggest that reciprocity, recruitment and selection, and performance appraisals have a significant relationship with KS behaviour. Furthermore, KS is independent of employees’ training and development along with incentive systems in organizations. The contribution of this paper is how certain HR practices and employees’ perceptions about reciprocity influence employees’ knowledge sharing in an organization. This paper assists employers, employees, policymakers, and scholars to understand the factors that can promote knowledge sharing. This study also highlights the significant role of Human Resource Practices (HRP).